DAMPAK PENGGUNAAN TIKTOK TERHADAP PEMBENTUKAN DAN PENGEMBANGAN IDENTITAS SISWA SMP NEGERI 5 MATARAM - Nisa, Hannatun; Rahmaniah, Hera Sukma; Najamudin, Hulul; Fidyatun; Septiana, Dini Iza; Jayanti, Ferlina; Edy Herianto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to find out the impact of the use of TikTok in shaping and developing the national identity of junior high school students, especially students at SMPN 5 Mataram. The method used in this study is qualitative descriptive, in collecting data is carried out by going directly to the field to conduct interviews and observations. The results of this study show that TikTok has an impact on the development and development of students' national identity. In this case, the use of the Tiktok application has an impact on students' understanding of national identity. There are 3 factors in determining the level of student understanding of national identity: (1) through student responses, (2) peer influence, and (3) student activeness in using the Tiktok application.